Industrial Design Protection in Indonesia: A Fiqh Perspective and its Challenges in Facing Communalistic Values - Husnul Haq; Muchtim Humaidi; Ali Muchtar (Justicia Islamica, 2023)
As a member of the World Trade Organization and a signatory to the TRIPs Agreement, the Indonesian Government drafted Law Number 31 of 2000 concerning industrial design. The establishment of TRIPs was the desire of industrial countries such as America and Europe to protect their products and strengthen their monopolistic position in international trade. Besides that, the philosophical foundation of TRIPs is based on individualism, while the social reality of the Indonesian nation adheres to a communalistic way of life. This research aims to describe industrial design protection in Indonesia and its problems from a fiqh perspective. This research is a legal research based on primary and secondary legal materials. Researchers also examined Law No. 31 of 2000 concerning industrial design and the Academic Paper of the Draft Law on Industrial Design in 2015. In data analysis, the authors use descriptive and comparative techniques. This study finds that although the Law of industrial design originates from the rules of the TRIPs Agreement, it generally does not conflict with Islamic jurisprudence but is in harmony with it. However, there are problems in protecting industrial design. To solve these problems, it is necessary to improve the industrial design law by considering national interests, improve the legal structure by increasing the professionalism of judges and judicial staff, and improve legal culture through education, socialization of legal regulations, good examples, and halal industrial designs.